Locally Delivered Tetracycline Fibres in the Treatment of Chronic Periodontitis - Kafle, Shristi; Pradhan, Shaili; Gupta, Sujaya (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Background: Chronic periodontitis is a highly prevalent and recurrent form of periodontal disease and locally delivered tetracycline fibres are considered to exert tremendous benefits for its treatment. Aim: The aim of the study was to observe the clinical results of locally delivered tetracycline fibres in the treatment of chronic periodontitis. Materials and Methods: Patients aged 35-54 years diagnosed with chronic periodontitis of both gender fulfilling the inclusion criteria were selected. A sample size of 30 was calculated and total number of 60 posterior sites were selected. These sites were divided into two sets in a split mouth design as control sites treated with SRP alone and test sites treated with SRP plus tetracycline fibres. Results: A combination of scaling, root planing and local drug delivery in the form of tetracycline fibres resulted in added benefits in the control of chronic periodontitis on the basis of the clinical findings from this study. Conclusion: This study further adds to the evidence that tetracycline fibres as locally delivered agent are safe and effective adjunct to scaling and root planing, and can produce significant clinical benefits when compared to scaling and root planing alone in the treatment of chronic periodontitis.